Regression‐Based Tests of the Market Pricing of Accounting Numbers: The Mishkin Test and Ordinary Least Squares - KRAFT, ARTHUR; LEONE, ANDREW J.; WASLEY, CHARLES E. (Journal of Accounting Research, 2007)
ABSTRACT The test developed in Mishkin [1983] (hereafter, MT) is widely used to test the rational pricing of accounting numbers. However, contrary to the perception in the accounting literature, the exclusion of variables from the MT's forecasting and pricing equations leads to an omitted variables problem that affects inferences about the rational pricing of accounting variables. Only if the omitted variables are rationally priced is their exclusion irrelevant. Failure to recognize this issue leads accounting researchers to employ the MT without appreciating how omitted variables affect the inferences they draw. We demonstrate that when additional explanatory variables are included in the MT, the rational pricing of accruals is not rejected. That is, the accrual anomaly documented in Sloan [1996] vanishes when additional explanatory variables are incorporated into the MT. We also show that in accounting research settings, where samples are large, ordinary least squares (OLS) is equivalent to the MT. As a result, accounting researchers should consider using OLS or be more explicit about the exact advantages of the MT over OLS in their research setting.